Fatwa Majelis Ulama Indonesia (MUI) tentang Pengharaman Salam Lintas Agama: Analisis Sosiologis-Teologis: The Indonesian Ulema Council's Fatwa on the Prohibition of Interfaith Greetings: A Socio-Theological Analysis - Armayanto, Harda; Wardhani, Selmarisa (Journal of Islamic and Occidental Studies, 2024)
This article aims to examine the theological and sociological aspects of the Indonesian Ulema Council (MUI) fatwa on the prohibition of interfaith greetings. This is based on the response of some people who consider the fatwa to have the potential to damage religious relations in Indonesia and threaten the existence of Pancasila. This article is qualitative in nature and based on library research (printed and digital data). At first, the author describes the history of interfaith greetings in Indonesia, the MUI fatwa related to interfaith greetings, and the arguments of the fatwa's opponents. From there, the author then analyzes the interfaith greetings theologically and sociologically, and then critically examines the arguments of the opponents of the MUI fatwa. In this paper, it is found that the fatwa departs from theological concerns by mixing the teachings of religions (syncretism). MUI considers salam as a prayer that contains aspects of ubudiah. Sociologically, MUI's fatwa is not problematic as alleged. This is because MUI is always actively committed to cooperate with all elements of a multicultural and multi-religious nation while still adhering to Islamic law.